Book review: Ethical Inquiries after Wittgenstein, edited by Salla Aldrin Salskov, Ondřej Beran and Nora Hämäläinen - Backström, Joel (Nordic Wittgenstein Review, 2024)
Review of Salla Aldrin Salskov, Ondřej Beran and Nora Hämäläinen (eds.), Ethical Inquiries after Wittgenstein